Maximum Peak Systolic Velocity and Management of Highly Vascularized Retained Products of Conception. (7th August 2015) - Van den Bosch, Thierry; Van Schoubroeck, Dominique; Timmerman, Dirk
Abstract : Objectives: The purpose of this study was to evaluate blood loss and procedure‐related complications during and after surgical removal of retained products of conception with high‐velocity enhanced myometrial vascularity. Methods: We conducted a prospective study of 18 consecutive women with a diagnosis of retained products of conception and enhanced myometrial vascularity, with a peak systolic velocity (PSV) higher than 60 cm/s. All underwent ultrasound‐guided surgical removal of the retained products under general anesthesia. Blood loss during the procedure was collected and recorded. The removed tissue was sent for histologic examination. An ultrasound examination was repeated within 24 hours. Results: Five patients had retained products of conception after a term delivery, 1 after a second‐trimester termination of pregnancy, 7 after a spontaneous first‐trimester miscarriage, and 5 after a first‐trimester termination elsewhere. The PSV in the area of enhanced myometrial vascularity at diagnosis ranged from 61.0 to 152.6 cm/s (mean, 104.9 cm/s). The estimated blood loss at surgery ranged from 20 to 1000 mL (mean, 200 mL). After surgery, the PSV in the myometrium dropped dramatically (≤30 cm/s in all but 1 case). In all cases, trophoblastic tissue was confirmed at histologic examination. Conclusions: Although surgical removal of retained products of conception was uneventful in most cases, heavy bleeding has to be anticipated in cases of high‐velocity flow in the myometrium underlying residual trophoblastic tissue. Accordingly, in cases of high‐velocity enhanced myometrial vascularity, we advocate surgical removal of the residual tissue under ultrasound guidance by an experienced surgeon and in the presence of a fully informed anesthetist.